Environmentally friendly flame retardant, preparation method and application thereof in plastics
By combining nanohydrotalcite intercalation modification and polytetrafluoroethylene, an environmentally friendly flame retardant was prepared, which solved the problems of large amount of existing flame retardant addition and poor environmental protection, and achieved halogen-free and smoke-free The high-efficiency flame retardant effect is suitable for plastic applications.
Patent Information
- Application Number
- CN202311537167.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-17
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-11-17
AI Technical Summary
The existing flame retardant is added in large amounts and poor environmental protection, and needs to be used in combination with flame retardants present in halogen, which may cause harm to the environment.
Nanohydrotalc is modified by dihydrogen phosphate, and amino groups are introduced, combined with polytetrafluoroethylene and melamine formaldehyde resin to prepare an environmentally friendly flame retardant, using DOPO's phosphine bond and modified nanowater The amino reaction of talc forms high reactivity and achieves flame retardant effect.
The prepared environmentally friendly flame retardant is halogen-free and smoke-free, environmentally friendly, anti-dripping, and excellent flame retardant performance. It can generate phosphorus-containing free radicals in the gas phase and condensed phase to form a carbon layer, inhibit combustion, and is non-toxic and harmless.
Smart Images

Figure CN117467196B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of flame retardants, in particular to an environmentally friendly flame retardant, a preparation method and application thereof in plastics. Background Art
[0002] Flame retardant is an additive used in the processing of polymer materials such as plastic fibers. Its main function is to enhance the flame retardant properties of polymer materials. DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is an organic compound with a biphenyl and phosphaphenanthrene structure. It has excellent heat resistance and flame retardant effects. The PH bond in its structure is highly reactive and can react with a variety of reactive groups to generate DOPO derivatives to enhance the flame retardant effect. Intumescent flame retardant is a new type of green and environmentally friendly flame retardant. It mainly achieves flame retardant effect by catalyzing the condensed phase to form a carbon layer and decomposing the gas phase to produce inert gas to block oxygen.
[0003] Chinese patent CN112724468B discloses a composite environmentally friendly flame retardant for PP and a PP flame retardant plastic, which are obtained by mixing dimethyl trimethylsilylmethylphosphonate, pentaerythritol melamine phosphate, magnesium hydroxide, aluminum hydroxide, antimony trioxide, magnesium sulfate whisker halogen-free flame retardant, and graphene. However, the addition amount of the composite environmentally friendly flame retardant is large, and 20% needs to be added to have a good flame retardant effect. In addition, the price of antimony trioxide is high and the environmental protection is poor. Chinese patent CN103788408B discloses a DOPO modified inorganic flame retardant and a preparation method thereof. DOPO is bonded or directly bonded to inorganic particles having hydroxyl groups on the surface through an alkenyl silane coupling agent to prepare a DOPO modified inorganic flame retardant. However, the modified flame retardant needs to be used in combination with a bromine-antimony flame retardant to have a good flame retardant effect. Due to the presence of halogen in the system, the bromine-antimony flame retardant may produce hydrogen halide gas during flame retardancy, which causes damage to the environment. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an environmentally friendly flame retardant, a preparation method and its application in plastics, which solves the problem of large amount of flame retardant added in the prior art and improves the environmental protection problem of the flame retardant.
[0005] In order to achieve the above object, the present invention provides a method for preparing an environmentally friendly flame retardant, which comprises the following steps: firstly, intercalating and modifying nano hydrotalcite with dihydrogen phosphate, then surface-modifying the nano hydrotalcite after intercalation modification, and introducing amino groups to obtain surface-modified dihydrogen phosphate intercalated nano hydrotalcite; then, preparing a polytetrafluoroethylene emulsion by combining a polyoxyethylene ether surfactant and a polyvinyl alcohol aqueous solution with polytetrafluoroethylene micropowder, and dropping a melamine formaldehyde prepolymer solution, and causing an etherification reaction between the hydroxyl groups of the melamine formaldehyde prepolymer and the hydroxyl groups of the polyvinyl alcohol to react with each other. Vinyl fluoride is loaded on melamine formaldehyde resin to obtain polytetrafluoroethylene loaded on polyvinyl alcohol modified melamine formaldehyde resin; polytetrafluoroethylene loaded on polyvinyl alcohol modified melamine formaldehyde resin and surface modified dihydrogen phosphate intercalated nano hydrotalcite are prepared into a dispersion, and under the conditions of ice bath, triethylamine, dichloromethane and carbon tetrachloride, the phosphorus-hydrogen bond of DOPO reacts with the amino group of the surface modified dihydrogen phosphate intercalated nano hydrotalcite and the hydroxyl group of polytetrafluoroethylene loaded on polyvinyl alcohol modified melamine formaldehyde resin to connect DOPO and obtain an environmentally friendly flame retardant.
[0006] A method for preparing an environmentally friendly flame retardant comprises the following steps:
[0007] Step (1) mixing dihydrogen phosphate intercalated nano-hydrotalcite with deionized water, ultrasonically dispersing, adding an aminosilane coupling agent, reacting, filtering, and drying after the reaction to obtain a surface-modified dihydrogen phosphate intercalated nano-hydrotalcite;
[0008] Step (2) polytetrafluoroethylene powder, polyoxyethylene ether surfactant, polyvinyl alcohol aqueous solution and deionized water are stirred into an emulsion, and a melamine formaldehyde prepolymer solution is added dropwise. After the addition is completed, the pH value is adjusted to 3-4, and the reaction is carried out. After the reaction, the pH value is adjusted to 8-9, ammonia is introduced to continue the reaction, and after the reaction, the reaction is filtered, washed and dried to obtain polyvinyl alcohol modified melamine formaldehyde resin loaded with polytetrafluoroethylene;
[0009] Step (3) mixing the surface-modified dihydrogen phosphate intercalated nano-hydrotalcite, polyvinyl alcohol-modified melamine formaldehyde resin-loaded polytetrafluoroethylene and dichloromethane, and ultrasonically dispersing them to obtain a surface-modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol-modified melamine formaldehyde resin-loaded polytetrafluoroethylene dichloromethane dispersion;
[0010] The surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO and triethylamine are mixed, and carbon tetrachloride is added dropwise. During the addition, the temperature of the reaction system is controlled not to exceed 5°C. After the addition is completed, the reaction is carried out, and after the reaction, the reaction is filtered, washed and dried to obtain an environmentally friendly flame retardant.
[0011] Preferably, in the step (1), the mass ratio of dihydrogen phosphate intercalated nano-hydrotalcite, deionized water, and aminosilane coupling is 1-5:20-40:0.5-2.5, the aminosilane coupling agent includes any one of γ-aminopropyltriethoxysilane and γ-aminopropyltrimethoxysilane, the ultrasonic dispersion condition is ultrasonic treatment at a frequency of 20-40 kHz for 20-40 minutes, and the reaction condition is reaction at room temperature for 20-24 hours.
[0012] Preferably, the dihydrogen phosphate intercalated nano-hydrotalcite in step (1) is prepared by the following steps:
[0013] The nano hydrotalcite and deionized water are mixed, and after ultrasonic dispersion, a sodium dihydrogen phosphate aqueous solution is added, and the pH value is adjusted to 4, reacted, filtered, washed, and dried to obtain the dihydrogen phosphate intercalated nano hydrotalcite.
[0014] Preferably, the mass ratio of nano-hydrotalcite, deionized water and sodium dihydrogen phosphate aqueous solution is: 2-4:30-50:20-30, the conditions for ultrasonic dispersion are: ultrasonic treatment at a frequency of 20-40kHz for 20-40min, the concentration of sodium dihydrogen phosphate aqueous solution is 0.1mol / L, and the pH is adjusted using a 0.1mol / L nitric acid aqueous solution, and the reaction conditions are reacting at 96-100°C for 10-12h.
[0015] Preferably, in the step (2), the mass ratio of polytetrafluoroethylene powder, polyoxyethylene ether surfactant, polyvinyl alcohol aqueous solution, deionized water, and melamine formaldehyde prepolymer solution is 60-80:4-6:120-140:110-150:200-300, and the reaction conditions are 75-85°C for 1-3h, and the polyoxyethylene ether surfactant includes any one of polyoxyethylene lauryl ether and isomeric decanol polyoxyethylene ether.
[0016] Preferably, the melamine formaldehyde prepolymer solution in step (2) is prepared by the following steps:
[0017] Mixing formaldehyde aqueous solution, melamine and deionized water, adjusting the pH value to 8.5-9.0, and reacting to obtain a melamine formaldehyde prepolymer solution;
[0018] Preferably, the mass ratio of formaldehyde aqueous solution, melamine and deionized water is 290-610:120-140:200-320, and the reaction conditions are 75-85° C. for 30-60 min.
[0019] Preferably, in the step (3), the mass ratio of the surface-modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol-modified melamine formaldehyde resin-loaded polytetrafluoroethylene dichloromethane dispersion, DOPO, triethylamine, and carbon tetrachloride is 400-480:50-60:25-35:40-50, and the reaction conditions are room temperature for 12-16 hours.
[0020] Preferably, in the step (3), the surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion is prepared by surface modified dihydrogen phosphate intercalated nano hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene and dichloromethane in a mass ratio of 20-40:40-60:320-400.
[0021] Preferably, the present invention also discloses an environmentally friendly flame retardant prepared by the above preparation method.
[0022] Preferably, the environmentally friendly flame retardant is used in plastics.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention prepares an environmentally friendly flame retardant by compounding DOPO, surface-modified dihydrogen phosphate intercalated nano-hydrotalcite, polyvinyl alcohol-modified melamine formaldehyde resin, and polytetrafluoroethylene. The environmentally friendly flame retardant is environmentally friendly, non-toxic and smokeless, anti-drip, and has excellent flame retardant properties. Among them, DOPO is a halogen-free, non-toxic flame retardant with good compatibility with the polymer matrix. It can generate phosphorus-containing free radicals in the gas phase during combustion, and phosphorus-containing acids in the condensed phase, which promote carbon formation. However, it mainly achieves the purpose of flame retardancy through the gas phase flame retardant mechanism, so it cannot inhibit the molten droplets generated during polymer combustion. Polytetrafluoroethylene is difficult to burn and has excellent anti-dripping effect, but its surface energy is low and there are no reactive active sites, which is difficult to be wetted by molten plastic. Therefore, it needs to be modified to a certain extent. The polyvinyl alcohol-modified melamine formaldehyde resin is used to load polytetrafluoroethylene. On the one hand, it can improve the compatibility of polytetrafluoroethylene in the polymer matrix. On the other hand, the polyvinyl alcohol-modified melamine formaldehyde resin can be used as a gas source when heated. When heated, it can decompose to produce non-toxic and harmless inert gases such as nitrogen to inhibit combustion. Polyvinyl alcohol as a carbon source can be dehydrated to form a dense carbon layer and produce water vapor at the same time to play a role in cooling and oxygen barrier.
[0025] 2. When the surface-modified dihydrogen phosphate intercalated nano-hydrotalcite is heated, the hydroxyl and carbonate between the layers will be released to generate non-toxic gases such as carbon dioxide and water vapor, which play a role in cooling and oxygen blocking. At the same time, the intercalated dihydrogen phosphate can be used as an acid source to promote the dehydration of the polyvinyl alcohol-modified melamine formaldehyde resin to form a carbon layer. After the removal of the hydroxyl and carbonate, the structure of the hydrotalcite will change to form a porous solid, which can absorb a large amount of acidic, volatile gases, thick smoke, etc. generated during the combustion of the material, play a role in suppressing smoke and preventing it from escaping into the atmosphere. However, as an inorganic flame retardant, the surface-modified dihydrogen phosphate intercalated nano-hydrotalcite has poor compatibility with the polymer matrix. The surface modification of the surface using an aminosilane coupling agent improves its compatibility while also introducing silicon atoms into the system, which can also promote the formation of the carbon layer to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention is a flow chart of the preparation process of the surface-modified dihydrogen phosphate intercalated nano-hydrotalcite;
[0027] Figure 2 The present invention is a process flow chart of preparing polyvinyl alcohol modified melamine formaldehyde resin polyvinyl alcohol modified melamine formaldehyde resin loaded with polytetrafluoroethylene;
[0028] Figure 3 The present invention is a process flow chart of the preparation of the environmentally friendly flame retardant;
[0029] Figure 4 The flame retardant performance test results of the environmentally friendly flame retardants prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention are shown in FIG. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] This embodiment discloses a method for preparing an environmentally friendly flame retardant, comprising the following steps:
[0033] (1) Nano hydrotalcite and deionized water were mixed uniformly, ultrasonically dispersed at a frequency of 20 kHz for 40 min, stirred at a stirring speed of 300 r / min, heated to 80° C., 0.1 mol / L sodium dihydrogen phosphate aqueous solution was added dropwise within 2 h, the pH value was adjusted to 4 with 0.1 mol / L nitric acid aqueous solution, heated to 96° C. for 12 h, filtered, washed with deionized water until neutral, and dried at 50° C. for 10 h to obtain dihydrogen phosphate intercalated nano hydrotalcite, wherein the mass ratio of nano hydrotalcite, deionized water, and sodium dihydrogen phosphate aqueous solution was 2:30:20;
[0034] (2) mixing the dihydrogen phosphate intercalated nano-hydrotalcite and deionized water, and ultrasonically dispersing them at a frequency of 20 kHz for 40 min, adding γ-aminopropyltriethoxysilane, stirring and reacting at room temperature and a stirring speed of 300 r / min for 24 h, filtering, and drying at 80° C. for 4 h to obtain surface-modified dihydrogen phosphate intercalated nano-hydrotalcite, wherein the mass ratio of the dihydrogen phosphate intercalated nano-hydrotalcite, deionized water, and γ-aminopropyltriethoxysilane is 1:20:0.5;
[0035] (3) Polytetrafluoroethylene powder, polyoxyethylene lauryl ether, 10% polyvinyl alcohol aqueous solution and deionized water were mixed uniformly, stirred and emulsified at a stirring speed of 3000 r / min for 20 minutes to obtain a polytetrafluoroethylene dispersion emulsion, heated to 45°C in a water bath, and dripped with a 50°C melamine formaldehyde prepolymer solution at a stirring speed of 500 r / min within 2 hours, and a 10% hydrochloric acid aqueous solution was added to adjust the pH value of the reaction system to 3, and the temperature was slowly raised at a speed of 2°C / min. The mixture was heated to 75°C, kept warm for 3 hours, a 10% sodium hydroxide aqueous solution was added to adjust the pH value to 8, ammonia was introduced to continue the reaction for 10 minutes, the mixture was cooled and filtered, and washed with petroleum ether and deionized water successively, and dried at 70°C for 8 hours to obtain polyvinyl alcohol-modified melamine formaldehyde resin loaded with polytetrafluoroethylene, wherein the mass ratio of polytetrafluoroethylene powder, polyoxyethylene lauryl ether, 10% polyvinyl alcohol aqueous solution, deionized water, and melamine formaldehyde prepolymer solution was 60:4:120:110:200;
[0036] The melamine formaldehyde prepolymer solution is prepared by the following steps: uniformly mixing a 37% formaldehyde aqueous solution, melamine and deionized water, adding a 20% sodium hydroxide aqueous solution to adjust the pH value of the system to 8.5, heating to 75°C, reacting for 60 minutes, the reaction liquid is clear and transparent, and during the reaction, a 20% sodium hydroxide aqueous solution is added dropwise to maintain the pH value of the reaction liquid unchanged, thereby obtaining a melamine formaldehyde prepolymer solution, wherein the mass ratio of the 37% formaldehyde aqueous solution, melamine and deionized water is 290:120:200;
[0037] (4) The surface modified dihydrogen phosphate intercalated nano-hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene and dichloromethane are uniformly mixed, and ultrasonic dispersion is carried out at a frequency of 20 kHz for 30 minutes to obtain a surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion; the surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO and triethylamine are uniformly mixed, and the mixture is cooled to 4°C under ice-salt bath conditions, and carbon tetrachloride is added dropwise to ensure that the temperature of the reaction system does not exceed 5°C during the addition process. The addition is completed within 2 hours, and the temperature is raised to room temperature. The mixture was stirred for 16 hours, filtered, washed with saturated sodium bicarbonate aqueous solution, deionized water and ethanol respectively, and dried at 70°C for 14 hours to obtain an environmentally friendly flame retardant, wherein the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO, triethylamine, and carbon tetrachloride was 400:50:25:40; in the surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene, and dichloromethane was 20:40:320.
[0038] Example 2
[0039] This embodiment discloses a method for preparing an environmentally friendly flame retardant, comprising the following steps:
[0040] (1) Nano hydrotalcite and deionized water were mixed uniformly, ultrasonically dispersed at a frequency of 30 kHz for 30 min, stirred at a stirring speed of 300 r / min and heated to 85° C., 0.1 mol / L sodium dihydrogen phosphate aqueous solution was added dropwise within 2 h, the pH value was adjusted to 4 with 0.1 mol / L nitric acid aqueous solution, the temperature was raised to 97° C. for reaction for 11.5 h, filtered, washed with deionized water until neutral, and dried at 55° C. for 9 h to obtain dihydrogen phosphate intercalated nano hydrotalcite, wherein the mass ratio of nano hydrotalcite, deionized water, and sodium dihydrogen phosphate aqueous solution was 2.5:35:25;
[0041] (2) mixing the dihydrogen phosphate intercalated nano-hydrotalcite and deionized water, and ultrasonically dispersing them at a frequency of 30 kHz for 30 min, adding γ-aminopropyltriethoxysilane, stirring and reacting at room temperature and a stirring speed of 300 r / min for 23 h, filtering, and drying at 85° C. for 3.5 h to obtain a surface-modified dihydrogen phosphate intercalated nano-hydrotalcite, wherein the mass ratio of the dihydrogen phosphate intercalated nano-hydrotalcite, deionized water, and γ-aminopropyltriethoxysilane is 2:25:1;
[0042] (3) Polytetrafluoroethylene powder, polyoxyethylene lauryl ether, 10% polyvinyl alcohol aqueous solution and deionized water were mixed uniformly, stirred and emulsified at a stirring speed of 3000 r / min for 20 minutes to obtain a polytetrafluoroethylene dispersion emulsion, heated to 50°C in a water bath, and dripped with a 50°C melamine formaldehyde prepolymer solution at a stirring speed of 500 r / min within 2 hours, and a 10% hydrochloric acid aqueous solution was added to adjust the pH value of the reaction system to 4, and the temperature was slowly raised at a speed of 2°C / min. The mixture was heated to 80°C, kept warm for 2 hours, a 10% sodium hydroxide aqueous solution was added to adjust the pH value to 9, ammonia was introduced to continue the reaction for 15 minutes, the mixture was cooled and filtered, and washed with petroleum ether and deionized water successively, and dried at 75°C for 7 hours to obtain polyvinyl alcohol-modified melamine formaldehyde resin loaded with polytetrafluoroethylene, wherein the mass ratio of polytetrafluoroethylene powder, polyoxyethylene lauryl ether, 10% polyvinyl alcohol aqueous solution, deionized water, and melamine formaldehyde prepolymer solution was 65:5:130:120:225;
[0043] The melamine formaldehyde prepolymer solution is prepared by the following steps: uniformly mixing a 37% formaldehyde aqueous solution, melamine and deionized water, adding a 20% sodium hydroxide aqueous solution to adjust the pH value of the system to 9.0, heating to 80° C., reacting for 45 minutes, the reaction liquid is clear and transparent, and during the reaction, a 20% sodium hydroxide aqueous solution is added dropwise to maintain the pH value of the reaction liquid unchanged, thereby obtaining a melamine formaldehyde prepolymer solution, wherein the mass ratio of the 37% formaldehyde aqueous solution, melamine and deionized water is 370:125:230;
[0044] (4) The surface modified dihydrogen phosphate intercalated nano-hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene and dichloromethane are uniformly mixed, and ultrasonic dispersion is carried out at a frequency of 30 kHz for 20 minutes to obtain a surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion; the surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO and triethylamine are uniformly mixed, and the mixture is cooled to 3°C under ice-salt bath conditions, and carbon tetrachloride is added dropwise to ensure that the temperature of the reaction system does not exceed 5°C during the addition process. The addition is completed within 2 hours, and the mixture is heated to room temperature. The mixture was stirred for 15 hours, filtered, washed with saturated sodium bicarbonate aqueous solution, deionized water and ethanol respectively, and dried at 75°C for 13 hours to obtain an environmentally friendly flame retardant, wherein the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO, triethylamine, and carbon tetrachloride was 420:55:30:45; in the surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene, and dichloromethane was 25:55:340.
[0045] Example 3
[0046] This embodiment discloses a method for preparing an environmentally friendly flame retardant, comprising the following steps:
[0047] (1) Nano hydrotalcite and deionized water were mixed uniformly, ultrasonically dispersed at a frequency of 30 kHz for 30 min, stirred at a stirring speed of 300 r / min, heated to 85° C., 0.1 mol / L sodium dihydrogen phosphate aqueous solution was added dropwise within 2 h, the pH value was adjusted to 4 with 0.1 mol / L nitric acid aqueous solution, heated to 98° C. for 11 h, filtered, washed with deionized water until neutral, and dried at 60° C. for 8 h to obtain dihydrogen phosphate intercalated nano hydrotalcite, wherein the mass ratio of nano hydrotalcite, deionized water, and sodium dihydrogen phosphate aqueous solution was 3:40:25;
[0048] (2) mixing dihydrogen phosphate intercalated nano-hydrotalcite and deionized water, and ultrasonically dispersing them at a frequency of 30 kHz for 30 min, adding γ-aminopropyltrimethoxysilane, stirring and reacting at room temperature and a stirring speed of 300 r / min for 22 h, filtering, and drying at 90° C. for 3 h to obtain surface-modified dihydrogen phosphate intercalated nano-hydrotalcite, wherein the mass ratio of dihydrogen phosphate intercalated nano-hydrotalcite, deionized water, and γ-aminopropyltrimethoxysilane is 3:30:1.5;
[0049] (3) Polytetrafluoroethylene powder, isomeric decanol polyoxyethylene ether, 10% polyvinyl alcohol aqueous solution and deionized water were mixed uniformly, stirred and emulsified at a stirring speed of 2000 r / min for 30 minutes to obtain a polytetrafluoroethylene dispersion emulsion, heated to 50°C in a water bath, and added dropwise at a stirring speed of 500 r / min to complete the addition within 2 hours, and a 10% hydrochloric acid aqueous solution was added to adjust the pH value of the reaction system to 3.5, and the temperature was slowly raised at a speed of 2°C / min. The mixture was heated to 80°C, kept warm for 2 hours, a 10% sodium hydroxide aqueous solution was added to adjust the pH value to 8.5, ammonia was introduced and the reaction was continued for 15 minutes, the mixture was cooled and filtered, and washed with petroleum ether and deionized water successively, and dried at 80°C for 6 hours to obtain polyvinyl alcohol-modified melamine formaldehyde resin loaded with polytetrafluoroethylene, wherein the mass ratio of polytetrafluoroethylene powder, isomeric decanol polyoxyethylene ether, 10% polyvinyl alcohol aqueous solution, deionized water, and melamine formaldehyde prepolymer solution was 70:5:130:130:250;
[0050] The melamine formaldehyde prepolymer solution is prepared by the following steps: uniformly mixing a 37% formaldehyde aqueous solution, melamine and deionized water, adding a 20% sodium hydroxide aqueous solution to adjust the pH value of the system to 8.5, heating to 80° C., reacting for 45 minutes, the reaction liquid is clear and transparent, and during the reaction, a 20% sodium hydroxide aqueous solution is added dropwise to maintain the pH value of the reaction liquid unchanged, thereby obtaining a melamine formaldehyde prepolymer solution, wherein the mass ratio of the 37% formaldehyde aqueous solution, melamine and deionized water is 450:130:260;
[0051] (4) The surface modified dihydrogen phosphate intercalated nano-hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene and dichloromethane are uniformly mixed, and ultrasonic dispersion is carried out at a frequency of 30 kHz for 20 minutes to obtain a surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion; the surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO and triethylamine are uniformly mixed, and the mixture is cooled to 2° C. under ice-salt bath conditions, and carbon tetrachloride is added dropwise to ensure that the temperature of the reaction system does not exceed 5° C. during the addition process, and the addition is completed within 2 hours, and the mixture is heated to room temperature. The mixture was stirred for 14 hours, filtered, washed with saturated sodium bicarbonate aqueous solution, deionized water and ethanol respectively, and dried at 80°C for 12 hours to obtain an environmentally friendly flame retardant, wherein the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO, triethylamine, and carbon tetrachloride was 440:55:30:45; in the surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene, and dichloromethane was 30:50:360.
[0052] Example 4
[0053] This embodiment discloses a method for preparing an environmentally friendly flame retardant, comprising the following steps:
[0054] (1) Nano hydrotalcite and deionized water were mixed uniformly, ultrasonically dispersed at a frequency of 30 kHz for 30 min, stirred at a stirring speed of 300 r / min, heated to 85° C., 0.1 mol / L sodium dihydrogen phosphate aqueous solution was added dropwise within 2 h, the pH value was adjusted to 4 with 0.1 mol / L nitric acid aqueous solution, heated to 99° C. for 10.5 h, filtered, washed with deionized water until neutral, and dried at 65° C. for 7 h to obtain dihydrogen phosphate intercalated nano hydrotalcite, wherein the mass ratio of nano hydrotalcite, deionized water, and sodium dihydrogen phosphate aqueous solution was 3.5:45:25;
[0055] (2) mixing the dihydrogen phosphate intercalated nano-hydrotalcite and deionized water, and ultrasonically dispersing them at a frequency of 30 kHz for 30 min, adding γ-aminopropyltrimethoxysilane, stirring and reacting at room temperature and a stirring speed of 300 r / min for 21 h, filtering, and drying at 95° C. for 2.5 h to obtain surface-modified dihydrogen phosphate intercalated nano-hydrotalcite, wherein the mass ratio of the dihydrogen phosphate intercalated nano-hydrotalcite, deionized water, and γ-aminopropyltrimethoxysilane is 4:35:2;
[0056] (3) Polytetrafluoroethylene powder, isomeric decanol polyoxyethylene ether, 10% polyvinyl alcohol aqueous solution and deionized water were mixed uniformly, stirred and emulsified at a stirring speed of 2000 r / min for 30 minutes to obtain a polytetrafluoroethylene dispersion emulsion, heated to 50°C in a water bath, and added dropwise at a stirring speed of 500 r / min to complete the addition within 2 hours, and a 10% hydrochloric acid aqueous solution was added to adjust the pH value of the reaction system to 3.5, and the temperature was slowly raised at a speed of 2°C / min. The mixture was heated to 80°C, kept warm for 2 hours, a 10% sodium hydroxide aqueous solution was added to adjust the pH value to 8.5, ammonia was introduced and the reaction was continued for 15 minutes, the mixture was cooled and filtered, and washed with petroleum ether and deionized water successively, and dried at 85°C for 5 hours to obtain polyvinyl alcohol-modified melamine formaldehyde resin loaded with polytetrafluoroethylene, wherein the mass ratio of polytetrafluoroethylene powder, isomeric decanol polyoxyethylene ether, 10% polyvinyl alcohol aqueous solution, deionized water, and melamine formaldehyde prepolymer solution was 75:5:130:140:275;
[0057] The melamine formaldehyde prepolymer solution is prepared by the following steps: uniformly mixing a 37% formaldehyde aqueous solution, melamine and deionized water, adding a 20% sodium hydroxide aqueous solution to adjust the pH value of the system to 9.0, heating to 80° C., reacting for 45 minutes, the reaction liquid is clear and transparent, and during the reaction, a 20% sodium hydroxide aqueous solution is added dropwise to maintain the pH value of the reaction liquid unchanged, thereby obtaining a melamine formaldehyde prepolymer solution, wherein the mass ratio of the 37% formaldehyde aqueous solution, melamine and deionized water is 530:135:290;
[0058] (4) The surface modified dihydrogen phosphate intercalated nano-hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene and dichloromethane are uniformly mixed, and ultrasonic dispersion is carried out at a frequency of 30 kHz for 20 minutes to obtain a surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion; the surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO and triethylamine are uniformly mixed, and the mixture is cooled to 2° C. under ice-salt bath conditions, and carbon tetrachloride is added dropwise to ensure that the temperature of the reaction system does not exceed 5° C. during the addition process, and the addition is completed within 2 hours, and the mixture is heated to room temperature. The mixture was stirred for 13 hours, filtered, washed with saturated sodium bicarbonate aqueous solution, deionized water and ethanol respectively, and dried at 85°C for 11 hours to obtain an environmentally friendly flame retardant, wherein the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO, triethylamine, and carbon tetrachloride was 460:55:30:45; in the surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene, and dichloromethane was 35:45:380.
[0059] Example 5
[0060] This embodiment discloses a method for preparing an environmentally friendly flame retardant, comprising the following steps:
[0061] (1) Nano-hydrotalcite and deionized water were mixed uniformly, ultrasonically dispersed at a frequency of 40 kHz for 20 min, stirred at a stirring speed of 300 r / min and heated to 90° C., 0.1 mol / L sodium dihydrogen phosphate aqueous solution was added dropwise within 2 h, the pH value was adjusted to 4 with 0.1 mol / L nitric acid aqueous solution, the temperature was raised to 100° C. for reaction for 10 h, filtered, washed with deionized water until neutral, and dried at 70° C. for 6 h to obtain dihydrogen phosphate intercalated nano-hydrotalcite, wherein the mass ratio of nano-hydrotalcite, deionized water, and sodium dihydrogen phosphate aqueous solution was 4:50:30;
[0062] (2) mixing the dihydrogen phosphate intercalated nano-hydrotalcite and deionized water, and ultrasonically dispersing them at a frequency of 40 kHz for 20 min, adding γ-aminopropyltriethoxysilane, stirring and reacting at room temperature and a stirring speed of 300 r / min for 20 h, filtering, and drying at 100° C. for 2 h to obtain surface-modified dihydrogen phosphate intercalated nano-hydrotalcite, wherein the mass ratio of the dihydrogen phosphate intercalated nano-hydrotalcite, deionized water, and γ-aminopropyltriethoxysilane is 5:40:2.5;
[0063] (3) Polytetrafluoroethylene powder, polyoxyethylene lauryl ether, 10% polyvinyl alcohol aqueous solution and deionized water were mixed evenly, stirred and emulsified at a stirring speed of 3000 r / min for 20 minutes to obtain a polytetrafluoroethylene dispersion emulsion, heated to 55°C in a water bath, and dripped with a 50°C melamine formaldehyde prepolymer solution at a stirring speed of 500 r / min within 2 hours, and a 10% hydrochloric acid aqueous solution was added to adjust the pH value of the reaction system to 3.5, and the temperature was slowly raised at a speed of 2°C / min. The mixture was heated to 85°C, kept warm for 1 hour, a 10% sodium hydroxide aqueous solution was added to adjust the pH value to 8.5, ammonia was introduced and the reaction was continued for 20 minutes, the mixture was cooled and filtered, and washed with petroleum ether and deionized water successively, and dried at 90°C for 4 hours to obtain polyvinyl alcohol-modified melamine formaldehyde resin loaded with polytetrafluoroethylene, wherein the mass ratio of polytetrafluoroethylene powder, polyoxyethylene lauryl ether, 10% polyvinyl alcohol aqueous solution, deionized water, and melamine formaldehyde prepolymer solution was 80:6:140:150:300;
[0064] The melamine formaldehyde prepolymer solution is prepared by the following steps: uniformly mixing a 37% formaldehyde aqueous solution, melamine and deionized water, adding a 20% sodium hydroxide aqueous solution to adjust the pH value of the system to 8.5-9.0, heating to 85° C., reacting for 30 minutes until the reaction liquid becomes clear and transparent, and dripping a 20% sodium hydroxide aqueous solution during the reaction to maintain the pH value of the reaction liquid unchanged, to obtain the melamine formaldehyde prepolymer solution, wherein the mass ratio of the 37% formaldehyde aqueous solution, melamine and deionized water is 610:140:320;
[0065] (4) The surface modified dihydrogen phosphate intercalated nano-hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene and dichloromethane are uniformly mixed, and ultrasonic dispersion is carried out at a frequency of 40 kHz for 10 minutes to obtain a surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion; the surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO and triethylamine are uniformly mixed, and the mixture is cooled to 1°C under ice-salt bath conditions, and carbon tetrachloride is added dropwise to ensure that the temperature of the reaction system does not exceed 5°C during the addition process. The addition is completed within 2 hours, and the mixture is heated to room temperature. The reaction is carried out. 12h, filtered, washed with saturated sodium bicarbonate aqueous solution, deionized water and ethanol respectively, and dried at 90°C for 10h to obtain an environmentally friendly flame retardant, wherein the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO, triethylamine, and carbon tetrachloride is: 480:60:35:50; in the surface modified dihydrogen phosphate intercalated nano hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene-dichloromethane dispersion, the mass ratio of surface modified dihydrogen phosphate intercalated nano hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene, and dichloromethane is 40:40:400.
[0066] Comparative Example 1
[0067] This comparative example discloses a method for preparing an environmentally friendly flame retardant, comprising the following steps:
[0068] (1) Polytetrafluoroethylene powder, polyoxyethylene lauryl ether, 10% polyvinyl alcohol aqueous solution and deionized water were mixed uniformly, stirred and emulsified at a stirring speed of 3000 r / min for 20 minutes to obtain a polytetrafluoroethylene dispersion emulsion, heated to 50°C in a water bath, and dripped with a 50°C melamine formaldehyde prepolymer solution at a stirring speed of 500 r / min within 2 hours, and a 10% hydrochloric acid aqueous solution was added to adjust the pH value of the reaction system to 4, and the temperature was slowly raised at a speed of 2°C / min. The mixture was heated to 80°C, kept warm for 2 hours, a 10% sodium hydroxide aqueous solution was added to adjust the pH value to 9, ammonia was introduced to continue the reaction for 15 minutes, the mixture was cooled and filtered, and washed with petroleum ether and deionized water successively, and dried at 75°C for 7 hours to obtain polyvinyl alcohol-modified melamine formaldehyde resin loaded with polytetrafluoroethylene, wherein the mass ratio of polytetrafluoroethylene powder, polyoxyethylene lauryl ether, 10% polyvinyl alcohol aqueous solution, deionized water, and melamine formaldehyde prepolymer solution was 65:5:130:120:225;
[0069] The melamine formaldehyde prepolymer solution is prepared by the following steps: uniformly mixing a 37% formaldehyde aqueous solution, melamine and deionized water, adding a 20% sodium hydroxide aqueous solution to adjust the pH value of the system to 9.0, heating to 80° C., reacting for 45 minutes, the reaction liquid is clear and transparent, and during the reaction, a 20% sodium hydroxide aqueous solution is added dropwise to maintain the pH value of the reaction liquid unchanged, thereby obtaining a melamine formaldehyde prepolymer solution, wherein the mass ratio of the 37% formaldehyde aqueous solution, melamine and deionized water is 370:125:230;
[0070] (2) The polyvinyl alcohol modified melamine formaldehyde resin loaded with polytetrafluoroethylene and dichloromethane are uniformly mixed, and ultrasonic dispersion is performed at a frequency of 30 kHz for 20 minutes to obtain a polyvinyl alcohol modified melamine formaldehyde resin loaded with polytetrafluoroethylene dichloromethane dispersion; the polyvinyl alcohol modified melamine formaldehyde resin loaded with polytetrafluoroethylene dichloromethane dispersion, DOPO, and triethylamine are uniformly mixed, and the mixture is cooled to 3° C. under ice-salt bath conditions, and carbon tetrachloride is added dropwise to ensure that the temperature of the reaction system does not exceed 5° C. during the addition process, and the addition is completed within 2 hours, and the mixture is heated to room temperature. The mixture was reacted for 15 hours, filtered, washed with saturated sodium bicarbonate aqueous solution, deionized water and ethanol respectively, and dried at 75°C for 13 hours to obtain an environmentally friendly flame retardant, wherein the mass ratio of polyvinyl alcohol-modified melamine formaldehyde resin-loaded polytetrafluoroethylene dichloromethane dispersion, DOPO, triethylamine and carbon tetrachloride was 420:55:30:45; the mass ratio of polyvinyl alcohol-modified melamine formaldehyde resin-loaded polytetrafluoroethylene and dichloromethane in the polyvinyl alcohol-modified melamine formaldehyde resin-loaded polytetrafluoroethylene-dichloromethane dispersion was 80:340.
[0071] Comparative Example 2
[0072] This comparative example discloses a method for preparing an environmentally friendly flame retardant, comprising the following steps:
[0073] (1) Nano hydrotalcite and deionized water were mixed uniformly, ultrasonically dispersed at a frequency of 30 kHz for 30 min, stirred at a stirring speed of 300 r / min and heated to 85° C., 0.1 mol / L sodium dihydrogen phosphate aqueous solution was added dropwise within 2 h, the pH value was adjusted to 4 with 0.1 mol / L nitric acid aqueous solution, the temperature was raised to 97° C. for reaction for 11.5 h, filtered, washed with deionized water until neutral, and dried at 55° C. for 9 h to obtain dihydrogen phosphate intercalated nano hydrotalcite, wherein the mass ratio of nano hydrotalcite, deionized water, and sodium dihydrogen phosphate aqueous solution was 2.5:35:25;
[0074] (2) mixing the dihydrogen phosphate intercalated nano-hydrotalcite and deionized water, and ultrasonically dispersing them at a frequency of 30 kHz for 30 min, adding γ-aminopropyltriethoxysilane, stirring and reacting at room temperature and a stirring speed of 300 r / min for 23 h, filtering, and drying at 85° C. for 3.5 h to obtain a surface-modified dihydrogen phosphate intercalated nano-hydrotalcite, wherein the mass ratio of the dihydrogen phosphate intercalated nano-hydrotalcite, deionized water, and γ-aminopropyltriethoxysilane is 2:25:1;
[0075] (3) The surface modified dihydrogen phosphate intercalated nano-hydrotalcite is mixed with dichloromethane, and ultrasonically dispersed at a frequency of 30 kHz for 20 minutes to obtain a dichloromethane dispersion of the surface modified dihydrogen phosphate intercalated nano-hydrotalcite. The surface modified dihydrogen phosphate intercalated nano-hydrotalcite dichloromethane dispersion, DOPO, and triethylamine are mixed evenly, cooled to 3°C under ice-salt bath conditions, and carbon tetrachloride is added dropwise to ensure that the temperature of the reaction system does not exceed 5°C during the addition process. The addition is completed within 2 hours, and the temperature is raised to room temperature. , react for 15 hours, filter, wash with saturated sodium bicarbonate aqueous solution, deionized water and ethanol respectively, and dry at 75°C for 13 hours to obtain an environmentally friendly flame retardant, wherein the mass ratio of surface modified dihydrogen phosphate intercalated nano-hydrotalcite dichloromethane dispersion, DOPO, triethylamine, and carbon tetrachloride is 420:55:30:45; the mass ratio of surface modified dihydrogen phosphate intercalated nano-hydrotalcite and dichloromethane in the surface modified dihydrogen phosphate intercalated nano-hydrotalcite dichloromethane dispersion is 80:340.
[0076] In all the above embodiments and comparative examples, the nano-hydrotalcite is from Tianjin Jinheng Blue Ocean Technology Co., Ltd., with the item number JH-79, the sodium dihydrogen phosphate is from Shanghai Jizhi Biochemical Technology Co., Ltd., with the CAS number 13472-35-0, the γ-aminopropyltrimethoxysilane is from Shanghai Aladdin Biochemical Technology Co., Ltd., with the CAS number 13822-56-5, the γ-aminopropyltriethoxysilane is from Shanghai Aladdin Biochemical Technology Co., Ltd., with the CAS number 919-30-2, the formaldehyde aqueous solution is from Shandong Yinghong Chemical Co., Ltd., with the item number 69981, the melamine is from Beijing Bailingwei Technology Co., Ltd., with the CAS number 108-78-1, and the polytetrafluoroethylene powder is from PTFE-0143 was obtained from Nanjing Tianshi New Material Technology Co., Ltd., polyoxyethylene lauryl ether was obtained from Hai'an Petrochemical Plant in Jiangsu Province, CAS No. 9002-92-0, isomeric decanol polyoxyethylene ether was obtained from Hai'an Petrochemical Plant in Jiangsu Province, product No. E-1005, polyvinyl alcohol was obtained from Nantong Runfeng Petrochemical Co., Ltd., CAS No. 9002-89-5, DOPO was obtained from Jiangyin Hanfeng Technology Co., Ltd., CAS No. 35948-25-5, triethylamine was obtained from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 121-44-8, and carbon tetrachloride was obtained from Shanghai Myril Biochemical Technology Co., Ltd., CAS No. 53-23-5.
[0077] Test example
[0078] The flame retardancy performance of the environmentally friendly composite flame retardant prepared in Examples 1-5 and Comparative Examples 1-2 was tested:
[0079] Test 1, combustion grade test: The environmentally friendly flame retardants prepared in Examples 1-5 and Comparative Examples 1-2 were added to polypropylene resin (PP), respectively, and the mass ratio of the environmentally friendly flame retardant to PP was 10:90. The performance test was performed according to GB / T2408-2008 "Determination of combustion performance of plastics by horizontal and vertical methods". The test results are shown in Table 1:
[0080] Table 1
[0081]
[0082] As can be seen from Table 1, the environmentally friendly flame retardant prepared by the present invention has a good flame retardant effect. When the addition amount is 10%, the vertical combustion grade of PP can reach V-0. As can be seen from Example 2 and Comparative Example 1, with the decrease of the content of the surface-modified dihydrogen phosphate intercalated nano-hydrotalcite in the flame retardant, the flame retardant effect of the flame retardant is reduced, because the dihydrogen phosphate between the nano-hydrotalcite layers is the main source of the acid source. Although DOPO can also produce some phosphoric acid compounds when heated, the main flame retardant mechanism of DOPO is the gas phase flame retardant mechanism, the content of the generated phosphoric acid compounds is small, and the effect of promoting the dehydration of the carbon source is limited, so the flame retardant effect is reduced. As can be seen from Example 2 and Comparative Example 2, with the decrease of the content of polytetrafluoroethylene loaded on the polyvinyl alcohol modified melamine formaldehyde resin in the flame retardant, the flame retardant effect of the flame retardant is reduced. This is because the flame retardant mode of DOPO and the modified nano-hydrotalcite is mainly the gas phase flame retardant mechanism, which cannot suppress the droplets generated by the combustion of the resin, so the flame retardant effect is reduced.
[0083] Test 2, oxygen index determination: The environmentally friendly flame retardants prepared in Examples 1-5 and Comparative Examples 1-2 were added to polypropylene resin (PP), respectively, and the mass ratio of the environmentally friendly flame retardant to PP was 10:90. The performance test was performed according to GB / T2406-93 "Plastic Combustion Performance Test Method Oxygen Index Method", and the test results are shown in Table 2:
[0084] Table 2
[0085]
[0086] As shown in Table 2, the environmentally friendly flame retardant prepared by the present invention has a good flame retardant effect. When the addition amount is 10%, the oxygen index of the flammable PP resin can be increased to 27.3%. It can be seen from Examples 1-5 and Comparative Examples 1-2 that with the increase of the ratio of the surface-modified dihydrogen phosphate intercalated nano-hydrotalcite and the polyvinyl alcohol-modified melamine formaldehyde resin to the polyvinyl alcohol-modified melamine formaldehyde resin loaded with polytetrafluoroethylene in the flame retardant, the limiting oxygen index of the PP resin first increases and then decreases. This is because the polyvinyl alcohol-modified melamine formaldehyde resin loaded with polytetrafluoroethylene has a stronger flame retardant effect than the surface-modified phosphorus. However, the content of phosphate compounds produced by DOPO is relatively small, and the polyvinyl alcohol modified melamine formaldehyde resin cannot be quickly dehydrated and carbonized to form a dense carbon layer to inhibit combustion. Therefore, as the content of surface modified dihydrogen phosphate intercalated nano-hydrotalcite increases, the more intercalated dihydrogen phosphate there are, and the faster the dehydration rate of the polyvinyl alcohol melamine formaldehyde resin is. When the content of surface modified dihydrogen phosphate intercalated nano-hydrotalcite is too high, although the dehydration rate is sufficient, the content of polyvinyl alcohol melamine formaldehyde resin decreases, and the content of the carbon layer formed by dehydration also decreases, and the efficiency of inhibiting combustion is reduced.
[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an environmentally friendly flame retardant, characterized in that: The following steps are involved: Step (1) mixing dihydrogen phosphate intercalated nano-hydrotalcite with deionized water, ultrasonically dispersing, adding an aminosilane coupling agent, reacting, filtering, and drying after the reaction to obtain a surface-modified dihydrogen phosphate intercalated nano-hydrotalcite; Wherein, the mass ratio of dihydrogen phosphate intercalated nano-hydrotalcite, deionized water, and aminosilane coupling agent is 1-5:20-40:0.5-2.5; The dihydrogen phosphate intercalated nano-hydrotalcite is prepared by the following steps: The nano-hydrotalcite and deionized water are mixed, and after ultrasonic dispersion, a sodium dihydrogen phosphate aqueous solution is added to adjust the pH value to 4, react, filter, wash, and dry to obtain a dihydrogen phosphate intercalated nano-hydrotalcite, wherein the mass ratio of the nano-hydrotalcite, deionized water, and sodium dihydrogen phosphate aqueous solution is: 2-4:30-50:20-30; Step (2) polytetrafluoroethylene powder, polyoxyethylene ether surfactant, polyvinyl alcohol aqueous solution and deionized water are stirred into an emulsion, and a melamine formaldehyde prepolymer solution is added dropwise. After the addition is completed, the pH value is adjusted to 3-4, and the reaction is carried out. After the reaction, the pH value is adjusted to 8-9, ammonia is introduced to continue the reaction, and after the reaction, the reaction is filtered, washed and dried to obtain polyvinyl alcohol modified melamine formaldehyde resin loaded with polytetrafluoroethylene; The mass ratio of polytetrafluoroethylene powder, polyoxyethylene ether surfactant, polyvinyl alcohol aqueous solution, deionized water and melamine formaldehyde prepolymer solution is 60-80:4-6:120-140:110-150:200-300; Step (3) mixing the surface-modified dihydrogen phosphate intercalated nano-hydrotalcite, polyvinyl alcohol-modified melamine formaldehyde resin-loaded polytetrafluoroethylene and dichloromethane, and ultrasonically dispersing them to obtain a surface-modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol-modified melamine formaldehyde resin-loaded polytetrafluoroethylene dichloromethane dispersion; Wherein, the surface modified dihydrogen phosphate intercalated nano hydrotalcite, polyvinyl alcohol modified melamine formaldehyde resin loaded with polytetrafluoroethylene and dichloromethane are in a mass ratio of 20-40:40-60:320-400; The surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO, and triethylamine are mixed, carbon tetrachloride is added dropwise, the temperature of the reaction system is controlled not to exceed 5° C. after the addition is completed, the reaction is carried out, and after the reaction, the reaction is filtered, washed, and dried to obtain an environmentally friendly flame retardant; The mass ratio of the surface modified dihydrogen phosphate intercalated nano-hydrotalcite-polyvinyl alcohol modified melamine formaldehyde resin loaded polytetrafluoroethylene dichloromethane dispersion, DOPO, triethylamine and carbon tetrachloride is 400-480:50-60:25-35:40-50.
2. The method for preparing an environmentally friendly flame retardant according to claim 1, characterized in that: In the step (1), the aminosilane coupling agent includes any one of γ-aminopropyltriethoxysilane and γ-aminopropyltrimethoxysilane, the ultrasonic dispersion is performed at a frequency of 20-40 kHz for 20-40 min, and the reaction is performed at room temperature for 20-24 h.
3. The method for preparing an environmentally friendly flame retardant according to claim 1, characterized in that: In the step (1), when preparing the dihydrogen phosphate intercalated nano-hydrotalcite, the ultrasonic dispersion conditions are: ultrasonic treatment at a frequency of 20-40 kHz for 20-40 min, the concentration of the sodium dihydrogen phosphate aqueous solution is 0.1 mol / L, the pH is adjusted using a 0.1 mol / L nitric acid aqueous solution, and the reaction conditions are 96-100° C. for 10-12 h.
4. The method for preparing an environmentally friendly flame retardant according to claim 1, characterized in that: In the step (2), the reaction conditions are 75-85° C. for 1-3 hours, and the polyoxyethylene ether surfactant includes any one of polyoxyethylene lauryl ether and isomeric decanol polyoxyethylene ether.
5. The method for preparing an environmentally friendly flame retardant according to claim 1, characterized in that: The melamine formaldehyde prepolymer solution in step (2) is prepared by the following steps: The formaldehyde aqueous solution, melamine and deionized water are mixed, the pH value is adjusted to 8.5-9.0, and the mixture is reacted to obtain a melamine formaldehyde prepolymer solution.
6. The method for preparing an environmentally friendly flame retardant according to claim 5, characterized in that: The mass ratio of formaldehyde aqueous solution, melamine and deionized water is 290-610:120-140:200-320, and the reaction conditions are 75-85° C. and 30-60 minutes.
7. The method for preparing an environmentally friendly flame retardant according to claim 1, characterized in that: In the step (3), the reaction conditions are room temperature for 12-16 hours.
8. An environmentally friendly flame retardant prepared by the preparation method of the environmentally friendly flame retardant according to any one of claims 1 to 7.
9. Use of the environmentally friendly flame retardant according to claim 8 in plastics.
